An adaptive wrapper algorithm for file transfer applications to support optimal large file transfers - Ghobadi, Alireza; Eswaran, C.; Muthuvelu, Nithiapidary; Tan, Ian K. T.; Kee, Yong Lee (Electronics Telecommunications Research Inst, 161 Kajong-Dong, Yusong-Gu, Taejon, 305-350, South Korea, 2009)
The overall file transmission time between peer machines is affected by network conditions, file dispatching and retrieval systems, error detection and the processing capabilities of the peers. Improving the network condition or the peers' processing capabilities for speedup will incur higher cost. We introduce a Wrapper Algorithm for the dispatching and retrieval systems at the peers. The algorithm performs file compression-decompression, file split-merge and file chunk scheduling processes to speedup the file transfer time of large files. The Wrapper Algorithm is wrapped around RSYNC and the results reveal an overall reduction of file transfer time of up to 66%.